Nucleation kinetics of the β″ precipitate in dilute Mg–Y alloys: A kinetic Monte Carlo study. (15th March 2022) - Liao, Heting; Kimizuka, Hajime; Ishii, Akio; Du, Jun-Ping; Ogata, Shigenobu
Graphical abstract: Abstract: The β ″ precipitate is a primary strengthening precipitate in Mg–Y alloys. It nucleates as localized zigzag- and hexagonal-shaped clusters. Studies on the nucleation kinetics of β ″ precipitate are scarce. In this study, we applied the kinetic Monte Carlo (KMC) approach to explore the nucleation kinetics of the β ″ precipitates in the Mg–3.0 at.%Y system using a density functional theory-based interatomic potential. The time evolution of nucleation of the β ″ precipitates was characterized based on the KMC results. Using these results, we predicted the existence of an optimum temperature for the formation of the β ″ precipitates to be 550 K, at which the time necessary for nucleation is the shortest. Moreover, an upper temperature limit, above which the β ″ precipitates cannot nucleate, was computed as 700 K. This study explains precipitate nucleation in Mg–Y alloys at an atomic level and provides the theory for obtaining an optimal age-hardening response.